Medicinal biotechnology in antibiotics - Hairol, Nur Nazatul Najwa; Adnan, Nurul Aini; Norhelmi, Siti Aishah; Mohamed, Elizah; Mohd Fauzi, Noor Akhmazillah (Penerbit UTHM, 2022)
In the course of the most recent decade, the rise and spread of antibiotic resistance in bacteria has prompted another dread in the logical and medical communities as among individuals from the overall population. The development of biotechnology in producing antibiotics enhances the growth in the country's economy, society and pharmaceutical industry. Antibiotics such as penicillin which are commonly used in some drugs against pathogens are naturally created by microorganisms, while non-antibiotic antibacterial drugs like antiseptics and sulfonamides are fully synthetic. Rationally there are some benefits from the use of antibiotics. In general, antibiotics are classified as an integral class of antibacterial that are specifically used more in medical products and also in animal feed. In addition, advances in the human pharmaceutical industry will probably produce a detailed base understanding of the antibiotics for the individual and populations in the near future. The aim of this study is to provide an overview on antibiotics starting from its introduction, biotechnology used, advantages and antibiotics effects to today's society.